Estudio de Factibilidad para la Creación de la Carrera de Educación Musical Modalidad a Distancia, en el Área de la Educación , el Arte y la Comunicación de la Universidad Nacional de Loja, año 2009-2010. Lineamientos Alternativos - Pineda Albán, Roque Arulfo (2010)
In the investigation process was formulated as a main objective: Carry out feasibility study for the establishment of the Music Education Degree Distance Learning Mode in the Area of Education, Arts and Communication, National University of Loja, and that could be analyzed to verify that it is feasible creation. For this study, we used the scientific method which allowed us to achieve valid knowledge through reliable instruments, and was supported also with the analytic-synthetic methods to learn the knowledge of reality, the inductive-deductive method it used for problematization and construction guidelines for purposes and report the descriptive method. As basic tools for data retrieval technique was used surveys and interviews applied to managers, professors of music education, music education graduates of the career of music, the V semester students of technical and technological level of the Musical Conservatory "Salvador Bustamante Celi” and students of music academies in the city of Loja, using verbal communication. Document analysis was applied in the planning and structuring the curriculum to run the race of Music Education at a Distance, the same that allowed us to collect information relevant to this investigation. The main findings are that public educational institutions do not have sufficient number of specialized teachers, do not have adequate classrooms and a reduced time for musical instruction, added to this, the failure of Cultural Aesthetics by authorities and music education teachers, results that helped us to point out the conclusions and recommendations with logical rigor fundamentals suggest actions designed to change for the betterment of music education in our province of Loja and the country, through a feasibility study for the creation Career in Music Education Distance Learning mode in the Area of Education, Art and Communication from the National University of Loja. Finally we conclude that Ecuadorian music education in particular Loja province through a series of problems both in academic as well as order physical space, since for lack of funds from the state, public educational institutions can not cover with the urgent needs that demand the teaching of music.